The Socio-Economic Characteristics of First Nation Teen Mothers - Garner, Rochelle; Guimond, Eric; Senécal, Sacha (International Indigenous Policy Journal, 2013)
Using data from the 2006 Census, this study examines the socio-economic characteristics of First Nations and non-Aboriginal teenage mothers, and compares these to those of non-teenage mothers in a cohort of women aged 25 to 29 years old. Results indicated that First Nations women were more likely than non-Aboriginal women to be teenage mothers. In general, teenage mothers were less likely to have graduated high school, more likely to live in overcrowded housing, and in a home in need of major repair. Furthermore, teenage mothers had lower household incomes after adjusting for the composition the household. Characteristics also differed significantly between First Nations and non-Aboriginal women, as well as between Registered Indian women living on- and off-reserve.